2011
DOI: 10.1038/jhh.2010.132
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conjugated linoleic acid, a natural trans fat from milk and meat, on human blood pressure: results from a randomized crossover feeding study

Abstract: Cis-9, trans-11 conjugated linoleic acid (CLA) is a natural trans fatty acid that is largely restricted to ruminant fats and consumed in foods and supplements. Its role in blood pressure (BP) regulation is still unclear. We examined the effect of cis-9, trans-11 CLA on BP compared with oleic acid. A total of 61 healthy volunteers were sequentially fed each of 3 diets for 3 weeks, in random order, for a total of 9 weeks. The diets were identical except for 7% of energy (18.9 g in a diet of 10 MJ day -1 ) that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…In case of blood pressure, some researchers reported that CLA had no effect on the blood pressure of healthy young men (Raff et al, 2006), in young overweight women (Diaz et al, Downloaded by [RMIT University] at 04:10 13 August 2015 2008) or healthy volunteers (Engberink et al, 2012). However, Pfeuffer et al (2011) noted a reduction in blood pressure in obese male subjects relative to the baseline value.…”
Section: Effects Of Cla On Blood Pressurementioning
confidence: 93%
“…In case of blood pressure, some researchers reported that CLA had no effect on the blood pressure of healthy young men (Raff et al, 2006), in young overweight women (Diaz et al, Downloaded by [RMIT University] at 04:10 13 August 2015 2008) or healthy volunteers (Engberink et al, 2012). However, Pfeuffer et al (2011) noted a reduction in blood pressure in obese male subjects relative to the baseline value.…”
Section: Effects Of Cla On Blood Pressurementioning
confidence: 93%
“…Of these, four publications were generated from an intervention trial conducted in a group of healthy Dutch adults, each focusing on a different risk factor for CVD. Collectively, the results demonstrated that supplemental CLA ( cis -9, trans -11: trans -10, cis -12-CLA, 80:20), relative to sunflower oil high in oleic acid, had no effect on blood pressure ( 35 ) , insulin sensitivity ( 36 ) , plasma proteome ( 36 ) , inflammatory markers or oxidative stress ( 37 ) at a dose of 20·2 g/d for 3 weeks. Negative effects on lipoprotein profiles were observed in the same study, which include increased total cholesterol, LDL-cholesterol (LDL-C) and total:HDL-cholesterol (HDL-C) ratio compared with sunflower oil ( 36 , 38 ) .…”
Section: Does the Current Literature (Clinical And Preclinical Studiementioning
confidence: 97%
“… The consumption of skimmed milk enriched with 3 g of a 1:1 mixture of 9- cis , 11- trans and 10- trans , 12- cis for 24 weeks led to a decrease in body weight and total fat mass in healthy, overweight subjects who maintained habitual diets and exercise patterns. No adverse effects were observed ENGBERIN et al 2012 [ 65 ] Sixty-one healthy volunteers Double-blind, placebo controlled study The diets were identical except for 7 % of energy (18.9 g in a diet of 10 MJ/day) that was provided either by oleic acid, by industrial trans fatty acids or by 9- cis , 11- trans CLA. The effect of the CLA diet compared with the oleic acid diet was 0.11 mm Hg (95 % confidence interval: −1.27, 1.49) systolic and −0.45 mm Hg (−1.63, 0.73) diastolic.…”
Section: Evidences From Human Studiesmentioning
confidence: 99%